Large scale mining in Ghana: a review of the implications on the host communities - Mustapha Okyere; Jonathan Zinzi Ayitey; Benjamin Avurinyinbiik Ajabuin (Journal of Degraded and Mining Lands Management, 2021)
Following the implementation of the Structural Adjustment Program (SAP) in 1983, Ghana’s mining sector has experienced significant growth, making Ghana one of the 10-leading producers of gold globally and the largest in Africa since 2018. To this end, the mining industry has been contributing significantly to the country’s total export earnings and the overall Gross Domestic Product (GDP). Despite its contribution to the economy, mining in Ghana has been a subject of debate in the past few years due to its diverse impacts on the host communities. This study therefore conducted a review of the implications of large-scale mining in Ghana. Findings revealed that, mining activities gravely affect the quality of water in most mining communities due to the use of toxic substances such as mercury. Mining activities also destroy forest reserves and farmlands, cause respiratory diseases and death. The study therefore suggests an effective collaboration between all relevant stakeholders in monitoring mining activities to help mitigate the impacts on the host communities.